2017
DOI: 10.1097/md.0000000000006837
|View full text |Cite
|
Sign up to set email alerts
|

Retroperitoneal metastatic poorly differentiated carcinoma with β-human chorionic gonadotropin secretion presenting as a psoas abscess

Abstract: Rationale:Psoas abscesses generally arise from a contiguous intra-abdominal or pelvic infectious process or hematogenous spreading of bacteria. The serum β-human chorionic gonadotropin has been used to detect normal or ectopic pregnancy. It also can be utilized in following up carcinomas.Patient concerns:Here, we reported a case of a 47-year-old woman who presented with a left psoas mass presumptively diagnosed as an abscess secondary to lumbar tuberculosis In addition, the patient had abnormal increase of β-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Iliopsoas abscess is a relatively rare disorder that has a diversity of frequency depending on patients' race, gender, and preexisting diseases [1]. Sequential iliopsoas abscess has been reported in the immunological suppression in rheumatoid arthritis, cervical spondylosis infection, ulcerative colitis, malignant tumor cases, and cardiovascular disorders [22][23][24][25][26]. Our study demonstrated that undernutrition is an indicator for the possible presence of IPA; however, serum inflammatory markers may not be useful to differentiate IPA from other inflammatory responses.…”
Section: Discussionmentioning
confidence: 66%
“…Iliopsoas abscess is a relatively rare disorder that has a diversity of frequency depending on patients' race, gender, and preexisting diseases [1]. Sequential iliopsoas abscess has been reported in the immunological suppression in rheumatoid arthritis, cervical spondylosis infection, ulcerative colitis, malignant tumor cases, and cardiovascular disorders [22][23][24][25][26]. Our study demonstrated that undernutrition is an indicator for the possible presence of IPA; however, serum inflammatory markers may not be useful to differentiate IPA from other inflammatory responses.…”
Section: Discussionmentioning
confidence: 66%
“…The serum beta-human chorionic gonadotropin has been used to detect normal or ectopic pregnancy, and it can also be used in following up carcinomas. In a case presented by [ 37 ] the biopsy of the left psoas demonstrated metastatic or infiltrating poorly-differentiated carcinoma with the secretion of Beta human chorionic gonadotropin. The subsequent pathological examination of the neoplasm showed the same pathologic morphology.…”
Section: Resultsmentioning
confidence: 99%